LEVEL OF EFFECTIVENESS OF BANKING FINANCING PRODUCTS IN SOUTH SULAWESI COMPARATIVE STUDY OF SHARIA BANKING AND CONVENTIONAL BANKS - Aulia Rahmadani; Fadiah Toon; Muh. Indra Wansyah; Kamaruddin Kamaruddin (STIESA Press, 2025)
This study evaluated the effectiveness of financing products provided by Islamic and conventional banks in South Sulawesi, focusing on customer growth, asset performance, and financing trends. Data from 2023 showed that Islamic banks recorded a customer growth rate of 5.85%, reaching 49.12 million customers, compared to 4.22% growth for conventional banks with 13.47 million customers. Islamic banks also demonstrated a significant increase in their total assets, from Rp771.29 trillion in February 2023 to Rp851.54 trillion in February 2024. Despite this growth, conventional banks remained dominant in terms of total financing, achieving Rp21.07 trillion, while Islamic banks reached Rp1.45 trillion but with a higher growth rate of 15.89%. The findings indicate that Islamic banking is gaining increasing trust and preference, particularly in regions with a high Muslim population, driven by innovative product offerings and enhanced operational efficiency. However, conventional banks continue to leverage their scale and established market presence. The results highlight the opportunities for Islamic banks to further improve their competitiveness by addressing service speed and expanding product diversity, while conventional banks may benefit from adopting strategies tailored to local market demands. This study underscores the potential for both banking systems to foster financial inclusivity and adapt to evolving consumer needs in South Sulawesi.